Continuous positive airway pressure for children with undifferentiated respiratory distress in Ghana: an open-label, cluster, crossover trial. Issue 6 (June 2017) - Wilson, Patrick T; Baiden, Frank; Brooks, Joshua C; Morris, Marilyn C; Giessler, Katie; Punguyire, Damien; Apio, Gavin; Agyeman-Ampromfi, Akua; Lopez-Pintado, Sara; Sylverken, Justice; Nyarko-Jectey, Kwadwo; Tagbor, Harry; et al.
Summary: Background: In low-income and middle-income countries, invasive mechanical ventilation is often not available for children at risk of death from respiratory failure. We aimed to determine if continuous positive airway pressure (CPAP), a form of non-invasive ventilation, decreases all-cause mortality in children with undifferentiated respiratory distress in Ghana. Methods: This open-label, cluster, crossover trial was done in two Ghanaian non-tertiary hospitals where invasive mechanical ventilation is not routinely available. Eligible participants were children aged from 1 month to 5 years with a respiratory rate of more than 50 breaths per min in children 1–12 months old, or more than 40 breaths per min in children older than 12 months, and use of accessory muscles or nasal flaring. CPAP machines were allocated to one hospital during each study block, while the other hospital served as the control site. The initial intervention site was randomly chosen using a coin toss. 5 cm of water pressure was delivered via CPAP nasal prongs. The primary outcome measure was all-cause mortality rate at 2 weeks after enrolment in patients for whom data were available after 2 weeks. We also did post-hoc regression analysis and subgroup analysis of children by malaria status, oxygen saturation, and age. This study is registered withClinicalTrials.gov, numberNCT01839474 . Findings: Between Jan 20, 2014, and Dec 5, 2015, 2200 children were enrolled: 1025 at the intervention site and 1175 at the control site. Final analysis included 1021 patients in the CPAP group and 1160 patients in the control group. 2 weeks after enrolment, 26 (3%) of 1021 patients in the CPAP group, and 44 (4%) of 1160 patients in the control group, had died (relative risk [RR] of mortality 0·67, 95% CI 0·42–1·08; p=0·11). In children younger than 1 year, all-cause mortality was ten (3%) of 374 patients in the CPAP group, and 24 (7%) of 359 patients in the control group (RR 0·40, 0·19–0·82; p=0·01). After adjustment for study site, time, and clinically important variables, the odds ratio for 2-week mortality in the CPAP group versus the control group was 0·4 in children aged up to 6 months, 0·5 for children aged 12 months, 0·7 for children aged 24 months, and 1·0 for those aged 36 months. 28 patients (3%) in the CPAP group and 24 patients (2%) in the control group had CPAP-related adverse events, such as vomiting, aspiration, and nasal, skin, or eye trauma. No serious adverse events were observed. Interpretation: In the unadjusted analysis the use of CPAP did not decrease all-cause 2-week mortality in children 1 month to 5 years of age with undifferentiated respiratory distress. After adjustment for study site, time, and clinically important variables, 2-week mortality in the CPAP group versus the control group was significantly decreased in children 1 year of age and younger. CPAP is safe and improves respiratory rate in a non-tertiary setting in a lower-middle-income country. Funding: General Electric Foundation.